Analysis of influencing factors of subjective career unsuccessfulness of vocational college graduates from the Department of Navigation in China - Wang, Li; Ye, Jian-Hong; Lee, Yi-Sang; Miao, Cong-Jin (Frontiers in Psychology, 2022)
The marine talent cultivation and output in higher vocational colleges is an important support to build a strong maritime country and ensure the steady development of the shipping business industry. Vocational colleges should ensure effective career preparation and career guidance education for their students, and train them to acquire the professional abilities to work and adapt effectively and quickly in the future. Some studies show that many crew members experience a decline in job satisfaction, a low sense of achievement, and a series of negative subjective career feelings. Even more, some crew members have poor work performance or unsuccessful career development behaviors such as career change or resignation. This study examined the causes and influencing factors of these circumstances and might be a reference for schools to strengthen the quality of their training programs in the future. In-depth interviews with 12 vocational marine navigation college graduates were conducted, and grounded theory was used to code and analyze the collected interview information. Four types of influencing factors were identified: adaptation preparation, career adaptability, adaptation action, and the situational factor. The adaptation preparation factor could be categorized into psychology, determination, lack of certificates, and simple work; the career adaptability factor could be categorized into boring work, busyness, a big gap between expectations and reality, danger, promotion difficulty, poor interpersonal relationships, high pressure, and maladaptation to the surroundings; the adaptation action factor could be categorized into passive fatigue, lack of training, competition, confidence, and planning; while the situational factor could be categorized into the impact of the epidemic, low social status, lack of support from family, and advantages of living on land. To help the marine navigation students better adapt to their jobs and avoid subjective career unsuccessfulness, higher vocational colleges need to strengthen students’ mental health education, consolidate knowledge and skills training, encourage students to obtain more vocational competency certificates, enhance their interpersonal communication skills, do effective career planning, pay attention to physical exercise and safety awareness training, and adopt other career management and counseling suggestions.